1992
DOI: 10.1111/j.1432-1033.1992.tb17043.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural requirements for the occupancy of pituitary adenylate‐cyclase‐activating‐peptide (PACAP) receptors and adenylate cyclase activation in human neuroblastoma NB‐OK‐1 cell membranes

Abstract: In these structure activity studies, the 46 analogs of the 27‐amino‐acid form of the pituitary‐adenylate‐cyclase‐activating peptide, PACAP(1–27), and the 38‐amino‐acid form, PACAP(1–38), were either monosubstituted or bisubstituted at positions 1–3, 20 and 21 or N‐terminally shortened. All analogs were compared on human neuroblastoma NB‐OK‐1 cell membranes for their ability to occupy 125I‐[AcHis1]PACAP(1–27)‐labelled receptors (AcHis, Nα‐acetylhistidine) and to activate adenylate cyclase (in terms of potency a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
107
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(121 citation statements)
references
References 33 publications
(20 reference statements)
8
107
1
Order By: Relevance
“…The EC50 values for PACAP-27 mediated transglutaminase-catalysed amine incorporation (0.08 nM) and protein cross-linking activity (0.4 nM) are in-line with the affinity of PACAP-27 for the PAC1 receptor (Dickson et al, 2006;Dickson and Finlayson, 2009;Harmar et al, 2012). Furthermore, PACAP-27-induced TG2 activity was blocked by the PAC1 receptor antagonist PACAP 6-38 (Robberecht et al, 1992). Overall these data suggest that activation of TG2 by PACAP-27 is mediated via the PAC1 receptor.…”
Section: In Vitro Modulation Of Tg2 Transamidation Activity By the Pasupporting
confidence: 64%
“…The EC50 values for PACAP-27 mediated transglutaminase-catalysed amine incorporation (0.08 nM) and protein cross-linking activity (0.4 nM) are in-line with the affinity of PACAP-27 for the PAC1 receptor (Dickson et al, 2006;Dickson and Finlayson, 2009;Harmar et al, 2012). Furthermore, PACAP-27-induced TG2 activity was blocked by the PAC1 receptor antagonist PACAP 6-38 (Robberecht et al, 1992). Overall these data suggest that activation of TG2 by PACAP-27 is mediated via the PAC1 receptor.…”
Section: In Vitro Modulation Of Tg2 Transamidation Activity By the Pasupporting
confidence: 64%
“…Gallwitz et al (1990) have shown that the C-terminal fragment of the peptide is important for receptor binding of the hormone, but is not sufficient to transduce a biological action as does the intact peptide (raise in cyclic AMP levels in rat insulinoma RINm5F cells). It appears that as in the case of glucagon (Unson et al, 1989), of GIP (Schmidt et al, 1986(Schmidt et al, , 1987 and of other members of the VIP/glucagon peptide family (Christophe et al, 1989;Robberecht et al, 1992) also for GLP-1(7-36)amide an intact N-terminus is needed for signal transduction and biological action. Provided this, action of DPP IV inactivates GLPl(7-36)amide.…”
Section: Discussionmentioning
confidence: 99%
“…PACAP 38, PACAP 6-38 [51], and neuropeptide Y were purchased from Peninsula Laboratories (San Carlos, CA).…”
Section: Reagentsmentioning
confidence: 99%